Quantification of PD-1/PD-L1 Interaction between Membranes from PBMCs and Melanoma Samples Using Cell Membrane Microarray and Time-Resolved Förster Resonance Energy Transfer - Lissete Sánchez-Magraner; Miguel de la Fuente; Charles Evans; James Miles; Ane Elexpe; Maddalen Rodriguez-Astigarraga; Egoitz Astigarraga; Gabriel Barreda-Gómez (Analytica, 2021)
Melanoma is a carcinoma known to evade the host immune defenses via the downregulation of the immune response. One of the molecules involved in this mechanism is programmed cell death ligand 1 (PD-L1), which interacts with its receptor, programmed cell death protein 1 (PD-1), expressed on T cells, leading to a reduction in cytokine release and cytotoxic activity, as well as a halt in T-cell proliferation. The approved therapeutic monoclonal antibodies, such as pembrolizumab, target the PD-1/PD-L1 interaction and are revolutionizing cancer treatments. We developed an assay that provides a quantitative readout of PD-1/PD-L1 interactive states between cell membranes of human immune cells (peripheral blood mononuclear cells, PBMCs) and PD-L1-expressing samples. For this purpose, cell membrane microarrays (CMMAs) were developed from membranes isolated from a HT144 cell line and melanoma samples, and PD-L1 expression was quantified using immunofluorescence (IF). CMMAs were incubated with cell membranes of PBMCs expressing PD-1, and the interaction with PD-L1 was quantified by time-resolved Förster resonance energy transfer, in the presence and absence of pembrolizumab as a blocking drug. The developed assay was able to quantify the PD-1/PD-L1 interaction, and this engagement was disrupted in the presence of the blocking antibody. This demonstrates the potential of the method to analyze monoclonal antibody drugs, as well as the functional states of immune checkpoint regulators. Furthermore, our findings provide evidence to support the future implementation of this methodology for both drug discovery and immune system monitoring in cancer, transplantation, and inflammatory and autoimmune diseases.